Drivers of Sustainability Practices and SMEs: A Systematic Literature Review - Yadav, Neetu; Gupta, Kritesh; Rani, Leela; Rawat, Deewanshi (European Journal of Sustainable Development, 2018)
Formal SMEs contribute up to 60% of total employment and up to 40% of GDP in emerging economies (World Bank, 2015). Globalization council (2009) study reveals that SMEs have more flexibility than MNCs to easily adapt and change to meet important environmental & social targets. Thus, with the right strategy, SMEs can offer both economic prosperity and environmental protection. This raises an important question as to what drives SMEs to consider sustainability in their practices? The article aims at presenting a comprehensive list of numerous drivers identified globally by various researchers using the research technique of systematic literature review. The study intends to contribute to the knowledge base by providing comprehensive state-of-the-art views and findings in the area sustainability practices and their drivers particularly in the context of SMEs. Keywords: Sustainability Drivers, SMEs, Systematic Literature Review